The Need for Speed : A New Framework for Telecommunications Policy for the 21st Century - Litan, Robert E., 1950- (Book collections on Project MUSE., 2013)
The twenty-first-century telecommunications landscape is radically different from the one that prevailed as recently as the last decade of the twentieth century. Robert Litan and Hal Singer argue that given the speed of innovation in this sector, the Federal Communications Commission's outdated policies and rules are inhibiting investment in the telecom industry, specifically in fast broadband networks. This pithy handbookpresents the kind of fundamental rethinking needed to bring communicationspolicy in line with technological advances. Fast broadband has huge societal benefits, enab.